Histopathologic Delineation of the Transition Zone in Short-Segment Hirschsprung Disease - Kapur, Raj P.; Kennedy, Amy J. (Pediatric and developmental pathology, 2013)
Failure to completely resect the transition zone (TZ) between aganglionic and neuroanatomically normal bowel (“TZ pull-through”) is considered one reason for postoperative obstructive symptoms in Hirschsprung disease (HD). Despite years of study, the proximal boundary of the TZ remains nebulous, complicated by discordant, often subjective, histopathologic definitions. In order to objectively delineate the TZ, transverse sections at 1 cm intervals from the rectums of 9 non-HD autopsy subjects and resections from 15 infants with short-segment HD were immunostained with Hu (ganglion cell bodies) and glucose transporter 1 (Glutl) (perineurium of extrinsic nerves), and 6 putative features of TZ were examined: (1) aganglionosis of ≥1/8th circumference; (2) myenteric or submucosal hypoganglionosis; (3) hypertrophic submucosal nerves; (4) Glut1+ submucosal innervation; (5) submucosal hyperganglionosis; and (6) “ectopic” ganglia in lamina propria, muscularis propria, or serosa. In non-HD controls, Glut1+ submucosal innervation, hypertrophic nerves, partial circumferential aganglionosis, and hypoganglionosis were absent or restricted to the distal 2 cm. In contrast, all 6 neuropathologic features of TZ were identified proximal to the aganglionic segment in the majority of HD resections, but the length of the TZ ranged from 0 to 12 cm, depending on which neuropathologic feature was considered. Excluding submucosal hyperganglionosis and ectopic ganglia, the TZ was generally <5 cm. Many features of TZ cannot be excluded intraoperatively with a biopsy or a full-circumference frozen section. However, partial circumferential aganglionosis, severe myenteric hypoganglionosis, and hypertrophic submucosal nerves can, and probably should, be assessed in full-circumference frozen sections of the proximal resection margin, to reduce the likelihood of TZ pull-through.